Fig Leaf (Ficus carica Linn.) Extract as a Potential Alternative Treatment for Oral Thrush Caused by Candida albicans - Gusbakti Rusip; Shieny Lokanata; Vivin Lydia (Open Access Indonesian Journal of Medical Reviews, 2025)
Oral thrush, primarily caused by Candida albicans, is a common opportunistic fungal infection affecting the oral mucosa. The increasing resistance of C. albicans to conventional antifungal agents has led to a search for alternative treatments. Fig leaf (Ficus carica Linn.) has been traditionally used for its medicinal properties and has shown promising antifungal activity. This study aimed to evaluate the inhibitory potential of ethanol extract of fig leaf against C. albicans in vitro. Fig leaves were collected, dried, and extracted using ethanol. The extract was then screened for its phytochemical constituents. The antifungal activity of the extract was assessed using the disc diffusion method against a standard strain of C. albicans. Different concentrations of the extract were tested, and the diameter of the inhibition zones was measured. Data were analyzed using one-way ANOVA and post hoc LSD tests. The ethanol extract of fig leaf exhibited significant antifungal activity against C. albicans. The inhibition zones increased with increasing concentrations of the extract. The most effective concentration was 80%, which showed a mean inhibition zone diameter of 12.65 ± 1.22 mm. Phytochemical screening revealed the presence of flavonoids, triterpenoids/steroids, glycosides, saponins, and tannins in the extract. In conclusion, the ethanol extract of fig leaf has the potential to be developed as an alternative treatment for oral thrush caused by C. albicans. Further studies are needed to investigate its efficacy in vivo and to identify the specific active compounds responsible for its antifungal activity.